Readings for difference: an introduction to Argentine queer literary critic - Picallo, Ximena; Gallardo, Guido (Centro Interdisciplinario de Investigaciones en Género. IdIHCS (CONICET - UNLP). Facultad de Humanidades y Ciencias de la Educación, Universidad Nacional de La Plata, 2020)
Literary criticism -as rational discourse and autonomous practice- is a product of the modern world that is institutionally validated by the standardization of its critique. Moreover, these critique or modes of reading become the critical canon circulating and assume the capacity to direct not only what to read but also how to read it. In line with these arguments we are interested in outlining a genealogy of queer literary criticism in our country, thinking about its scope and the historical moment in which these texts are inscribed, visualized and legitimized within the Argentine literary critical canon.